2022
DOI: 10.1101/2022.07.10.499443
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Layer-specific, retinotopically-diffuse modulation in human visual cortex by emotional faces

Abstract: Emotionally expressive faces evoke enhanced neural responses in multiple brain regions, a phenomenon thought to depend critically on the amygdala. This emotion-related modulation is evident even in primary visual cortex (V1), providing a potential neural substrate by which emotionally salient stimuli can affect perception. How does emotional valence information, computed in the amygdala, reach V1? Here we use high-resolution functional MRI to investigate the layer profile and retinotopic distribution of neural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 118 publications
0
2
0
Order By: Relevance
“…Previous studies have found that emotion triggers distinct neural representations in the visual cortex (Bo et al, 2021;Kragel et al, 2019). These neural representations are valence-specific (Bo et al, 2022;Liu et al, 2022) and different visual cortical patterns encode at least 5 distinguishable emotion categories (Bo et al, 2022;Kragel et al, 2019;Liu et al, 2022)). Other types of affect appear to be embedded in early sensory pathways as well.…”
Section: Emotion Systemsmentioning
confidence: 99%
“…Previous studies have found that emotion triggers distinct neural representations in the visual cortex (Bo et al, 2021;Kragel et al, 2019). These neural representations are valence-specific (Bo et al, 2022;Liu et al, 2022) and different visual cortical patterns encode at least 5 distinguishable emotion categories (Bo et al, 2022;Kragel et al, 2019;Liu et al, 2022)). Other types of affect appear to be embedded in early sensory pathways as well.…”
Section: Emotion Systemsmentioning
confidence: 99%
“…The observed behavioral results and findings regarding valence and anxiety have important implications for understanding the neural mechanism of emotion processing. Many visual areas, including fusiform face area and early visual cortex, and subcortical regions, such as the amygdala, show greater activation to emotional faces, both positive and negative valenced, compared to neutral faces (Liu et al, 2022). Additionally, the amygdala-frontal connectivity has been a major focus for top-down emotion regulation through cognitive reappraisal.…”
Section: Conceptual Advance and Future Directionsmentioning
confidence: 99%